2016
DOI: 10.1016/j.fuproc.2015.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption performance indicators for the CO2/CH4 separation: Application to biomass-based activated carbons

Abstract: A deep understanding of the interaction and competition between different gases on adsorption processes is essential for the design and optimization of industrial units. Two biomass-derived activated carbons (CS-CO 2 and CS-H 2 O), synthesized in our laboratory, were evaluated as selective adsorbents for the separation of CO 2 from CO 2 /CH 4 mixtures. Adsorption isotherms of the pure gases (i.e., CO 2 and CH 4 ) were performed in a high-pressure magnetic suspension balance at three different temperatures (303… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 69 publications
2
52
0
Order By: Relevance
“…However, for a more precise evaluation the working capacities (differences between the gas uptakes of both components under adsorption and regeneration conditions) and the heat required for the regeneration of the adsorbent would also need to be taken into account [36].…”
Section: Selectivity To Co 2 Separationmentioning
confidence: 99%
“…However, for a more precise evaluation the working capacities (differences between the gas uptakes of both components under adsorption and regeneration conditions) and the heat required for the regeneration of the adsorbent would also need to be taken into account [36].…”
Section: Selectivity To Co 2 Separationmentioning
confidence: 99%
“…Previous research conducted in our laboratory has successfully demonstrated the great potential of cherry stone-based carbons for biogas upgrading. They were tested for their CO 2 and CH 4 equilibrium adsorption capacities at high pressures under static [19] and dynamic conditions in a purpose-built lab-scale fixed-bed unit [20].…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of CO 2 over CH 4 for the CNS at 1 bar and 30 • C was approximately 3.6. It was found that the value of selectivity was comparable to that of carbon-based adsorbents [49].…”
Section: Adsorption Selectivitymentioning
confidence: 74%